High-recognition and low-scattering quantum dot immunochromatography probe with tubular assembly structure as well as preparation method and application of high-recognition and low-scattering quantum dot immunochromatography probe
By using one-dimensional hollow tubular material and quantum dot assembly technology, the immune recognition efficiency and signal amplification effect of immunochromatography probes are improved, and the problem of insufficient sensitivity of existing probes in low-load virus detection is solved, and higher detection sensitivity and quantitative capabilities are achieved.
Patent Information
- Application Number
- CN202411642586.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing immunochromatography probes are insufficient in the detection of low-load viral antigens, and the signal amplification effect and immune recognition efficiency are low, resulting in a high false negative rate and weak quantitative ability.
One-dimensional hollow tubular material is used as the carrier of the signal probe, and the brightness and immune response efficiency of the probe are improved through a layer-by-layer assembly strategy mediated by affinity polymers, and controlled assembly of quantum dots is carried out through chemical means to prepare composite nanostructures with high load quantum dots.
It improves the immune recognition efficiency of signal probe-antigen immune complexes and capture antibodies, reduces the light scattering effect, significantly improves the sensitivity of the lateral flow immune chromatography platform, and supports the early detection, early treatment and early prevention and control of viral infections.
Smart Images

Figure CN119505869A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biological immune detection, and in particular relates to an immunochromatographic probe with high recognition and low scattering quantum dot tubular assembly structure, and a preparation method and application thereof. Background Art
[0002] Infectious diseases caused by viruses have become one of the most serious public health problems in the world, resulting in a large loss of life and economy. As a mature and popular on-site detection method, lateral flow immunochromatography (LFIA) has the advantages of being rapid, portable, low-cost and user-friendly, and is widely used in personal health self-examination. In traditional detection, colloidal gold nanoparticles (AuNPs) are widely used in colorimetric LFIA detection. However, colloidal gold test strips have limited sensitivity, high false negative rate, weak quantitative ability, and it is difficult to achieve high-sensitivity detection. With the development of nanomaterials, many new materials such as upconversion luminescent materials and time-resolved fluorescent labeling materials have been used as LFIA markers, which greatly promoted the development of LFIA and achieved high-sensitivity detection of targets, but it usually requires instrument-side design, which is highly complex and costly. In contrast, quantum dots have a series of unique optical properties, such as high fluorescence quantum yield, large molar extinction coefficient, large Stokes shift, etc., making them one of the ideal immunochromatographic labeling materials. Unfortunately, it is still difficult to achieve effective detection of low-load viral antigens by LFIA simply from the perspective of assembly amplification and signal integration of signal elements without considering the immune recognition efficiency. Therefore, we should explore the overall optimization of signal amplification and immune recognition efficiency from the shape dimension of the signal tag, so as to obtain the theory and method to improve the sensitivity of LFIA.
[0003] Studies have shown that the inherent signal strength of the signal probe and the efficiency of the immune reaction with the capture antibody on the test site (T) are considered to be two important factors that determine the sensitivity of LFIA. Especially when the concentration of the target analyte is close to the detection limit (LOD), since the amount of the target analyte is much less than the amount of the antibody on the surface of the signal probe, the target analyte in the sample solution is completely captured by the signal probe, and it is generally believed that the amount of analyte bound to the surface of each signal probe is the same. Therefore, in the LOD state, the binding affinity between the capture antibody sprayed on the T line and the formed signal probe-antigen immune complex is considered to be the most critical factor in determining the sensitivity of LFIA. Since the pores of the nitrocellulose membrane (NC membrane) in the immunochromatographic platform can be approximately regarded as a complex tubular channel, the dimension of the signal probe will affect the flux of the signal probe. Therefore, designing a probe of the correct dimension to match the tubular channel of the NC membrane and ensuring that the signal probe has good fluidity in the pore size of the NC membrane is conducive to improving the recognition probability of the probe-antigen immune complex and the capture antibody. John C.Bischof's research group concluded through model simulation that, usually when the probe size is greater than 100nm, the capture of the signal probe-antigen immune complex by the capture antibody at the test site will be limited by the diffusion rate. Since the diffusion rate of the traditional signal probe from the bulk solution to the fixed target on the surface of the nitrocellulose membrane (NC membrane) is slow, it brings about a seriously underestimated diffusion-related limitation at the level of immune response kinetics, which will greatly weaken the sensitivity of the test strip. The probe designed by the present invention has excellent diffusion rate and immune response kinetics, which is beneficial to improve the immune recognition efficiency of the signal probe-antigen immune complex and the capture antibody, and plays a vital role in improving the sensitivity of LFIA.
[0004] At present, the mainstream carriers of commercial immunochromatographic probes are three-dimensional spherical templates with a size of 200-400nm (such as polystyrene balls, silica microspheres, etc.), which have the advantages of good dispersibility, excellent stability, and easy functionalization. For example, the polymer-embedded fluorescent microspheres (100-400nm) developed by BangsLabs in the United States, and the colored latex microspheres (200-300nm) commonly used by immunochromatographic reagent companies such as Aotai Biotech and Wondfo Biotech in China all belong to this category. In the field of academic research, Li et al. assembled fluorescent materials by electrostatic adsorption through surface modification of polystyrene balls; Yu's research team assembled fluorescent materials in the internal cavity and surface of silica nanospheres through chemical bonding. Although these materials are helpful to improve the sensitivity of LFIA as signal probes, they still have obvious performance defects. This is because the pores of NC membranes are intricate, and their sizes can be distributed between tens to thousands of nanometers depending on the model of the membrane. For example, the commonly used NC membrane models: CN95 and CN140, whose pore sizes are about 15um and 8um. The three-dimensional spherical structure material is a uniform dimensional structure. When the traditional submicron-level sphere passes through the intricate tubular channels of the NC membrane, it is restricted in the three dimensions of length, width, and height. That is, any dimension blocked by the pores will cause it to be retained and blocked on the membrane. Therefore, it does not have selective permeability, resulting in a sharp decrease in the number of signal probe-antigen immune complexes participating in the immune reaction between the test line and the capture antibody, and a significant decrease in the efficiency of the immune reaction. At the same time, this part of the signal probe-antigen immune complex that blocks the tubular channels of the NC membrane will cause a high background signal on the test strip, reducing the signal-to-noise ratio of the test strip. In addition, it has been proved by theory and experiment that the diffusion kinetics of the three-dimensional spherical structure material are slower than those of the one-dimensional tubular structure material of the same size, and the recognition efficiency will be lower when the immune reaction is carried out at the test site.
[0005] From the perspective of signal amplification, most three-dimensional or two-dimensional materials have thick media and strong light scattering effects. When the fluorescent signal generated by the signal probe under ultraviolet excitation passes through this thick and uneven medium, part of the light will deviate from the original propagation direction and scatter around during the propagation, instead of directly propagating to the target collection position. The human eye or smart device receives the fluorescent signal for fixed-direction signal collection, so the light scattering phenomenon will affect the efficiency of signal collection and cause signal loss. In addition, the light scattering phenomenon caused by the thick silicon medium may also lead to a reduction in signal quality. When the light encounters this part of the medium, an interaction will occur, and light with the same frequency as the incident light but weaker intensity (called sub-waves) will be re-emitted in all directions. The uniformity and symmetry of this scattered light distribution depends on the relationship between the scale of the scattering particles and the wavelength of the incident light. When the scale of the scattering particles is much smaller than the wavelength of the incident light, molecular scattering or Rayleigh scattering occurs, and the scattered light distribution is uniform and symmetrical; when the scale of the scattering particles is comparable to the wavelength of the incident light, Mie scattering occurs, and the intensity distribution of the scattered light is asymmetric and complex. Therefore, these different types of scattering will affect the quality of the signal. In summary, for the current mainstream carriers of LFIA, due to the intrinsic properties of its materials, it has a strong light scattering effect, which will reduce the effect of signal amplification, which is rarely reported in previous work.
[0006] Based on the defects of the signal amplification effect and immune recognition efficiency of the above-mentioned materials, the present invention uses a one-dimensional hollow tubular material as a carrier of the signal probe. Due to its special one-dimensional structure, it is conducive to effectively passing through the intricate NC membrane tubular channel with the minimum cross-sectional dimension, and finally reaching the test line to react with the capture antibody. At the same time, due to its special one-dimensional hollow tubular structure, the diffusion rate of the obtained probe is improved, and it can fully react with the capture antibody when it reaches the test line. The combined effect of these two factors improves the immune recognition efficiency of the signal probe-antigen immune complex and the capture antibody, which is of great significance and value for effectively improving the sensitivity of LFIA. The present invention uses a one-dimensional hollow tubular material as a carrier of the signal label to reduce the interference of the light scattering effect. At the same time, we can use chemical means to carry out controllable assembly of quantum dots on one-dimensional hollow tubular materials, and prepare a composite nanostructure with high-load quantum dots to achieve better signal amplification effect. Due to the dual optimization of signal amplification effect and immune response efficiency, it is conducive to improving the sensitivity of the lateral flow immunochromatography platform, and provides an important scientific basis for early detection, early treatment and early prevention and control of viral infection. Summary of the invention
[0007] In view of the technical problems that the signal amplification effect and immune recognition efficiency of existing commercial traditional submicron-level uniform dimensional morphology probes are limited, the purpose of this application is to provide a high-recognition, low-scattering quantum dot tubular assembly structure immunochromatographic probe and its preparation method and application. The present invention has developed a one-dimensional hollow tubular quantum dot controllable assembly type labeling probe with high immune efficiency, low scattering effect and integrated assembly signal amplification; the present invention uses hollow silica nanotubes as carriers, utilizes low light scattering effect and large specific surface area, and adopts affinity polymer-mediated layer-by-layer assembly strategy to greatly improve the brightness of the labeling probe; at the same time, the probe has excellent pass rate and diffusion rate in the NC membrane, which improves the efficiency of immune response.
[0008] The present invention also constructs an immunochromatographic test strip with high quantitative sensitivity and low naked eye detection limit. First, a well-defined nickel-hydrazine complex nanorod is formed by a precipitation reaction in a reverse micelle, and then silica is coated using a sol-gel process. Silica is deposited around the nickel-hydrazine complex to stabilize the complex, thereby replicating the rod-like structure, and finally, by selective etching, a hollow silica nanotube with high uniformity and high yield is produced after the complex is dissolved. Then, by utilizing the driving force of chemical bonds, quantum dots are densely and uniformly assembled on the surface of the hollow silica nanotubes. Due to the low scattering effect of the hollow silica nanotubes and the layer-by-layer coordination-driven affinity assembly based on the polymer intermediate layer, the signal is maximized while maintaining the one-dimensional hollow tubular material structure of the material. A quantum dot high-density assembly and high fluorescence intensity oil phase assembly are constructed, and the assembly is transferred to an aqueous solvent by an efficient alkylsilane phase transfer strategy. The assembly is protected by depositing a thin and dense layer of silicon oxide on its surface, and a fluorescent probe is obtained by carboxylation and coupling the new coronavirus antigen N protein antibody based on this. Finally, the fluorescent probe obtained by this method was used in the sandwich lateral flow immunochromatography detection platform, and was visualized and quantified by the naked eye and smart device terminals, which has important significance and value for the early screening and diagnosis of new coronavirus antigens.
[0009] The technical solution adopted by the present invention is as follows:
[0010] The method for preparing a high-recognition, low-scattering quantum dot tubular assembly structure immunochromatographic probe comprises the following steps: reacting Ni salt with hydrazine hydrate in the presence of a surfactant to form nickel-hydrazine complex nanorods, then coating silica using a sol-gel process, and then selectively etching with hydrochloric acid to obtain one-dimensional hollow tubular silica nanotubes SNTs; performing thiol modification on the SNTs to obtain SNTs-SH, using SNTs-SH as a carrier and CdSe / CdS / ZnS red quantum dots (QDs) as signal tags, performing multilayer assembly of quantum dots on the carrier SNTs-SH to construct an oil-soluble tubular assembly dSi / tQD, and then using n-octyltrimethoxysilane OTMS to cause a hydrolysis-condensation reaction on the surface of the tubular assembly to achieve a phase transfer of the tubular assembly from an organic phase to an aqueous phase, and then performing a reaction with the tubular assembly to obtain an oil-soluble tubular assembly dSi / tQD. The method utilizes tetraethyl orthosilicate (TEOS) to hydrolyze and deposit a thin layer of silica to improve the stability of the internally assembled quantum dots. Then, the amino groups are modified by 3-aminopropyltriethoxysilane and the carboxyl groups are modified by succinic anhydride to obtain STQS-COOH. The carboxyl-modified assembly STQS-COOH is coupled to a labeled antibody and blocked with a blocking solution containing BSA to finally obtain a probe.
[0011] Furthermore, the method for preparing the one-dimensional hollow tubular silica nanotubes SNTs specifically comprises the following steps:
[0012] S1: dissolving the surfactant Brij58 in cyclohexane, stirring at 45-55°C, adding Ni salt, and then adding hydrazine hydrate dropwise, stirring and reacting for 2.8-3.2h, so that the Ni salt reacts with hydrazine hydrate to form nickel-hydrazine complex nanorods;
[0013] S2: then add diethylamine and TEOS to the system of step S1, continue stirring and reacting for 1.5-2.5 hours to allow the silicon dioxide to precipitate, centrifuge and wash after the reaction is completed;
[0014] S3: The product obtained in step S2 is dispersed in a 0.8-1.2M hydrochloric acid solution, stirred at room temperature for 0.5-2h for selective etching, and then the product is collected by centrifugation and washed with water until the pH is neutral to obtain one-dimensional hollow tubular silica nanotubes SNTs, which are stored in anhydrous ethanol.
[0015] Furthermore, in step S1, the surfactant is Brij58, and its solubility concentration in cyclohexane is 0.5-0.6 g / mL. The molar ratio of hydrazine hydrate to Ni salt is 4-10:1, and the solubility concentration of Ni salt in cyclohexane is 50-100 mmol / L.
[0016] Further, the volume ratio of diethylamine to TEOS in step S2 is 0.4-0.6:1, the volume ratio of TEOS in step S2 to the amount of Ni salt in step S1 is 1:0.5-0.8, the volume unit is mL, and the amount unit is mmol.
[0017] Furthermore, the process of multi-layer assembly of quantum dots on the template SNTs-SH is as follows:
[0018] 1) Assembly of the first layer of quantum dots: Take a toluene solution of CdSe / CdS / ZnS quantum dots, add the template SNTs-SH, and ultrasonicate for 7-10 minutes to obtain a uniform solution, then collect the precipitate by centrifugation, and after the residual toluene solvent in the precipitate evaporates, an assembly of a layer of quantum dots SNTs / QD1 is obtained; the mass ratio of the template SNTs-SH to the CdSe / CdS / ZnS quantum dots is 1:0.8-1.0;
[0019] 2) Coating of amino dendritic polymer: adding the assembly product obtained in step 1) to an ethanol solution containing amino dendritic polymer polyamide PAMA-NH2, ultrasonicating for 7-10 minutes, and removing the supernatant by centrifugation to obtain the nanocomposite SNTs / QD-PAMA with the outermost layer coated by amino groups, and then using the amino groups rich on its surface to coordinate with quantum dots, the subsequent assembly of quantum dots is continued;
[0020] 3) Repeat the above steps 1)-2) to achieve multi-layer alternating assembly of quantum dots in the organic phase and amino dendritic polymer polyamide PAMA-NH2, assembling a total of 2-4 layers of quantum dots, preferably assembling 3 layers of quantum dots, and finally obtaining the constructed oil-soluble assembly SNTs / tQD product.
[0021] Furthermore, the carboxyl-modified assembly is coupled with a labeled antibody and blocked with a blocking solution containing BSA: the carboxyl-modified assembly is added to a pH = 6.0 PB buffer, NHs and EDC are added, and the mixture is incubated on a shaker for 20 to 40 minutes; the product is then collected by centrifugation; the product is resuspended in a pH = 7.4 PB buffer, the labeled antibody is added, and the mixture is reacted on a shaker for 2 to 3 hours; after the reaction is completed, the mixture is centrifuged and blocked with a pH = 7.4 PB buffer containing 0.5-2% BSA for 1.5 to 3 hours; the tubular probe is then collected by centrifugation, washed with a pH = 7.4 PB buffer, and stored in a refrigerator in a pH = 7.4 PB buffer.
[0022] The present invention also provides an application of the above-mentioned high recognition, low scattering quantum dot tubular assembly structure immunochromatographic probe, wherein the probe is used to detect the corresponding antigen, comprising the following steps:
[0023] S1 Construction of immunochromatographic test strip: The immunochromatographic test strip includes a sample pad, a NC membrane and an absorption pad assembled in sequence on a plastic base plate, and the T line and C line of the NC membrane are coated with a capture antibody and a goat anti-mouse IgG antibody, respectively;
[0024] S2 antigen concentration detection: dilute the antigen with pH=7.4 PBS buffer containing 0.05-0.2% sodium caseinate, 0.1-1% BSA, 0.1-1% Tween 20 and 0.1-0.5% PVP360, prepare a series of standard solutions with different antigen concentrations, add the probe to the standard solution and mix thoroughly, drip it onto the sample pad of the test strip respectively, flow to the absorption pad through the NC membrane under capillary action, after 5-20 minutes, use a smart phone to take pictures under the excitation of 365nm excitation light of ultraviolet lamp, obtain images of T line and C line of the test strip, use ColorPicker, a color recognition software of the smart phone, to read the R value of the photo image of the T line, and draw a standard curve with R value as the ordinate and antigen concentration as the abscissa.
[0025] Furthermore, the labeled antibody is monoclonal antibody 2 of SARS-CoV-2NP, the capture antibody is monoclonal antibody 1 of SARS-CoV-2NP, and the antigen is SARS-CoV-2NP antigen.
[0026] The present invention starts from the perspective of the probe's dimension, and the designed probe has excellent pass rate and excellent immune response kinetics in the lateral flow immunochromatography platform (LFIA), thereby improving the immune response efficiency of LFIA. While reducing the interference of the light scattering effect, the quantum dots are controllably assembled, greatly improving the signal intensity of a single material. Due to the dual optimization of the signal amplification effect and the immune response efficiency, the present invention is conducive to improving the sensitivity of LFIA, and provides an important scientific basis for the early detection, early treatment and early prevention and control of viral infections.
[0027] The beneficial effects achieved by the present invention are:
[0028] 1) The present invention forms nickel-hydrazine complex crystal nanorods in reverse micelles through surfactant end-capping, and then obtains hollow silica nanotubes through silica coating and selective etching. The nanorods are used as nanocarriers, and quantum dots are used as nanosignal primitives. By studying the light scattering effect of the hollow silica nanotubes and the high-density, uniform and controllable assembly of the quantum dots, the fluorescence intensity of the tubular assembly material is improved to the greatest extent from the dimension of signal amplification, and the problem of serious reduction in the fluorescence intensity of the material caused by the light scattering phenomenon of other solid templates is effectively solved.
[0029] 2) The present invention studies the immune capture efficiency and immune response kinetics of hollow tubular materials and solid spherical materials in solutions and test strips, and verifies that the immune capture efficiency and immune response kinetics of one-dimensional hollow tubular materials are greater than those of three-dimensional solid spherical materials, which provides important theoretical guidance and experimental basis for using them as immune capture probes to improve the sensitivity of lateral flow immunochromatography platforms.
[0030] 3) The present invention constructs a sandwich lateral flow immunochromatography detection platform, which comprehensively optimizes the design and synthesis of probes from the dimensions of signal amplification and immunodynamics, without introducing additional or complicated operations and steps. It uses the simplest and most effective method to greatly improve the sensitivity of sandwich lateral flow immunochromatography test strips, and is expected to be widely used in the fields of biological detection medicine and biosensors.
[0031] 4) The labeled probes of commercial lateral flow immunochromatography test strips are mostly colloidal gold or rare earth fluorescent microspheres. Due to their weak signal amplification ability, low immune capture efficiency, slow immune reaction kinetics and other problems, the test strips have limited sensitivity, high false negative rate, weak quantitative ability, and it is difficult to achieve high-sensitivity detection. Therefore, there is an urgent need to develop a material with simple synthesis and excellent performance as a labeled probe for the lateral flow immunochromatography platform to improve the sensitivity and quantitative ability of the strip. Starting from the synthesis and design of the signal probe, the present invention conducts comprehensive regulation through the light scattering effect, immune capture efficiency, immune reaction kinetics and other dimensions of nanomaterials. The designed labeled probe has good immune capture efficiency and chemical reaction kinetics performance on the basis of improving the signal amplification ability. The synthesis process steps are simple and controllable, and it has broad prospects in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the synthesis route of the STQS tubular assembly according to an embodiment of the present invention;
[0033] Figure 2 It is a comparative diagram of the immunoassay principle of the hollow tubular assembly probe of the present invention and the existing solid spherical assembly probe;
[0034] Figure 3 These are TEM images of the products at various stages in the preparation process of the STQS tubular assembly in Example 1 of the present invention; a) solid silicon tube template SNTs@Ni-N2H4, (b) hollow silicon tube template SNTs, (c) three-layer oil phase assembly SNTs / QD3, and (d) STQS tubular assembly structure.
[0035] Figure 4are the performance test results of the assemblies prepared under different quantum dot feed ratios; a) The relationship between quantum dot assembly rate and feed ratio (the inset is a daylight photograph of the supernatant after quantum dot assembly at each stage (top) and the assembly dispersed in toluene solution (bottom)); b) The relationship between the fluorescence intensity of the quantum dot assembly and the quantum dot assembly rate.
[0036] Figure 5 These are the test results of the fluorescence properties of different quantum dot materials in Example 3 of the present invention; a) fluorescence spectra of STQS assembly structures of hydrophobic quantum dots and their derivatives with red (R), green (G) and blue (B); b) fluorescence spectra of STQS nanomaterials at different stages (the percentage content on the graph is defined as: the first curve is the fluorescence intensity of 100% loaded free quantum dots, and the percentage content of the remaining stages is the fluorescence intensity relative to the first curve).
[0037] Figure 6 It is a graph showing the relationship between the fluorescence intensities of hollow tubular assembly structures and solid spherical assembly structures with different numbers of particles (the same number of quantum dots are uniformly assembled from a single material in Example 4 of the present invention) for the verification of the shape light scattering effect; Figure 6 The slope ratio of the fitting curve in the middle is the signal amplification factor. The illustration above the fitting curve: the upper left is a daylight photograph of the hollow tubular assembly structure solution, and the lower left is a fluorescence photograph of the solution; the upper right of the illustration is a daylight photograph of the solid spherical assembly structure solution, and the lower right is a fluorescence photograph of the solution. The middle illustration of the fitting curve: a schematic diagram of the experimental principle.
[0038] Figure 7 It is a verification of the immunodynamics of the shape effect solution, a relationship diagram between the hollow tubular assembly structure and the solid spherical assembly structure with the same number of particles (the same number of quantum dots are uniformly assembled in a single material in Example 4 of the present invention) and the fluorescence intensity of the streptavidin-FITC fluorescent dye in the reaction supernatant (the middle of the fitting curve is a schematic diagram of the experimental principle).
[0039] Figure 8 It is the relationship between the R value signal intensity and the number of particles on the detection line of the hollow tubular assembly structure probe or the solid spherical assembly structure probe (the single material in Example 4 of the present invention is uniformly assembled with the same number of quantum dots) in the biotin-streptavidin system; a) the test results of the hollow tubular assembly structure probe; b) the test results of the solid spherical assembly structure probe, the upper left illustration is the fluorescence image of the detection line of the two corresponding materials under ultraviolet light, and the lower illustration is a schematic diagram of the detection principle.
[0040] Fig. 9 It is a fluorescent photograph of the fluorescent lateral flow immunochromatographic test strip in the SARS-COV-2NP antigen concentration range of 0-500ng / mL.
[0041] Fig.10The smartphone ColorPicker color reading software was used to read the linear and nonlinear fitting curves of the T line R value and different concentrations of SARS-COV-2NP antigen.
[0042] Fig.11 The linear and nonlinear fitting curves of the T line R signal intensity and different concentrations of SARS-COV-2NP antigen were measured using a commercial reader. DETAILED DESCRIPTION
[0043] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0044] In the embodiment of the present invention, the concentration of ammonia water is 25-28%.
[0045] The structural schematic diagram of the synthesis route of the STQS tubular assembly in the embodiment of the present invention is shown in Figure 1 .
[0046] Schematic diagram of immunoassay principle comparison between the hollow tubular probe of the present invention and the existing solid spherical probe Figure 2 , Figure 2 The labeled antibody is first coupled to the middle material to obtain a probe, and then the probe and antigen are specifically combined. The corresponding capture antibodies are respectively laid on the test strips C and T to form a double antibody sandwich immune structure for detection.
[0047] Embodiment 1:
[0048] 1. Synthesis of Hollow Silica Nanotubes (SNTs) Template
[0049] Step 1) Synthesis of nickel-hydrazine@silica nanotubes: 8.5 g of Brij58 was dissolved in 15 mL of cyclohexane and stirred at 50° C., 1.5 mL of NiCl2·6H2O aqueous solution (concentration of 0.8 mol / L) was added, and then 0.45 mL of hydrazine hydrate (hydrazine concentration of 64%) was added dropwise, stirred for 3 hours, and then 1 mL of diethylamine and 2 mL of tetraethyl silicate (TEOS) were added to the system, and the reaction was continued to be stirred. The silica coating process was carried out for 2 hours, and the obtained product was centrifuged and washed with isopropanol to obtain nickel-hydrazine@silica nanotubes, marked as solid silica tube template SNTs@Ni-N2H4.
[0050] Step 2) Etching of nickel-hydrazine@silica nanotubes: The solid silica tube template SNTs@Ni-N2H4 was dispersed in 300 mL of HCl (1 mol / L) aqueous solution, the dispersion was stirred at room temperature for 1 hour, the product was collected by centrifugation, and washed with water until the pH was neutral to obtain hollow silica nanotubes SNTs (i.e., hollow silica tube template SNTs), which were stored in anhydrous ethanol (dispersion concentration was about 10 mg / mL).
[0051] The TEM images of the solid silicon tube template SNTs@Ni-N2H4 and the hollow silicon tube template SNTs are shown in Figure 3 Part a and part b of .
[0052] 2. Synthesis of Thiolated Hollow Silica Nanotubes (SNTs-SH) Template
[0053] Take 18 mL of the above ethanol dispersion containing 180 mg of SNTs, add 182 mL of ethanol, 2 mL of ammonia water, and 200 uL of (3-mercaptopropyl) trimethoxysilane (MPS), and stir at 520 rpm for 12 hours at room temperature. Finally, collect the precipitate by centrifugation, wash it three times with ethanol, and obtain thiol-modified hollow silica nanotubes (SNTs-SH), which are dispersed in ethanol (dispersion concentration is about 10 mg / mL).
[0054] 3. Multilayer Ligand-Driven Affinity Assembly
[0055] Take 1 mL of the ethanol solution of SNTs-SH obtained in step 2, centrifuge to remove the supernatant to obtain a precipitate (about 10 mg SNTs-SH), place it in the air to dry slightly, add 1 mL (10 mg / mL) of toluene solution containing cadmium selenide / cadmium sulfide / zinc sulfide red quantum dots (QDs), and obtain a uniformly dispersed solution after ultrasonic treatment for 7 minutes. Remove the supernatant by centrifugation, wash with toluene to remove unbound QDs, and obtain an oil-soluble assembly (SNTs / QD1) with a layer of QDs. Add 2 mL of ethanol solution (3 mg / mL) of dendritic polyamide (PAMA-NH2) to the precipitate of the above SNTs / QD1 assembly, and obtain a uniformly dispersed solution after ultrasonic treatment for 10 minutes. Remove the supernatant by centrifugation, and wash with ethanol to remove excess PAMA-NH2 to obtain a nanocomposite (SNTs / QD1 / P) of SNTs-SH / QD1 / PAMA-NH2 coated with PAMA-NH2 on the outermost layer. Then, in order to assemble the second layer of QDs, 1 mL of toluene solution of red QDs (10 mg / mL) was added to the precipitate of SNTs / QD1 / P, and a uniformly dispersed solution was obtained after ultrasonic treatment for 7 min. The supernatant was removed by centrifugation, and the excess QDs were removed by washing with toluene to obtain an oil-soluble assembly (SNTs / QD2) of two layers of QDs. The above operation was repeated, and 2 mL of ethanol solution of dendritic polyamide (PAMA-NH2) (3 mg / mL) was added to the wet precipitate of the above SNTs / QD2 assembly. A uniformly dispersed solution was obtained after ultrasonic treatment for 10 min, the supernatant was removed by centrifugation, and the excess PAMA-NH2 polymer was removed by washing with ethanol to obtain a nanocomposite of SNTs-SH / QD2 / PAMA-NH2 (SNTs / QD2 / P). Finally, in order to assemble the third layer of QDs, 1 mL of toluene solution of red QDs (10 mg / mL) was added to the precipitate of SNTs / QD2 / P. After ultrasonic treatment for 7 min, a uniformly dispersed solution was obtained. The supernatant was removed by centrifugation, and the excess unbound QDs were removed by washing with toluene to obtain an oil-soluble assembly of three-layer QDs (SNTs / QD3).
[0056] The TEM image of the oil-soluble assembly SNTs / QD3 of the above-mentioned three-layer QDs is shown in Figure 3 Sub-figure c.
[0057] 4. Phase transfer of the assembly
[0058] 200 μL of octyltrimethoxysilane (OTMS) was added to the above oil-soluble assembly SNTs / QD3 precipitate, and ultrasonicated for several minutes until it was dissolved into a homogeneous solution. Subsequently, a mixed solution of 30 mL of methanol and 0.75 mL of ammonia water was added, and ultrasonic treatment was continued for 30 min. The precipitate was then collected by centrifugation, and the unbound OTMS was washed with methanol. The product was then dispersed in a mixed solution of 33 mL of water and 66 μL of sodium silicate, and the reaction was stirred at 400 rpm at room temperature for 18 h to form an organosilicon shell to obtain a surface silane-modified SNTs / QD3-OTMS complex.
[0059] 5. Preparation of STQS Tubular Assemblies
[0060] pass The SNTs / QD3-OTMS surface was grown by silane method. The SNTs / QD3-OTMS was centrifuged to remove the supernatant and ultrasonically dispersed in 20 mL of ethanol. Then 5 mL of water and 0.625 mL of ammonia water were added, and 25 μL of tetraethyl silicate (TEOS) was added for medium-speed stirring reaction. After an interval of 1 hour, TEOS was added again (25 μL of TEOS was added twice) for a total reaction of 2 hours. After the reaction was completed, the product was collected by centrifugation and then washed three times with ethanol to remove excess TEOS to obtain a STQS tubular assembly coated with silica on the surface.
[0061] The TEM image of the above STQS tubular assembly is shown in Figure 3 Sub-figure d.
[0062] Figure 3 The results can draw the following conclusions: 1) Comparison of sub-figure a→sub-figure b proves that the solid silicon tube template is transformed into a hollow silicon tube template through the etching step; 2) Comparison of sub-figure b→sub-figure c proves the assembly of quantum dots on the hollow silicon tube template; 3) Comparison of sub-figure c→sub-figure d proves that the tubular assembly is coated with silica.
[0063] The fluorescence spectra of the products at different stages in the preparation process of the above STQS tubular assembly can be found in Figure 5 b. Definition of percentage content on the spectrum: the first curve is the fluorescence intensity of 100% free quantum dots, and the percentage content of the remaining stages is the fluorescence intensity relative to the first curve. Figure 5 In b, QDs are bare quantum dots, SNTs / QD1 is a one-layer quantum dot assembly, SNTs / QD2 is a two-layer quantum dot assembly, SNTs / QD3 is a three-layer quantum dot assembly, SNTs / QD3-OTMS is a surface silane-modified complex, and STQS is a tubular assembly wrapped with silica on the surface. The ability of the SNTs-SH template to assemble multilayer quantum dots was investigated by measuring the fluorescence intensity at different assembly stages. Figure 5b As can be seen, we define 100% as the fluorescence intensity value of the oil phase quantum dots that are equal to the first layer without assembly. The fluorescence intensity of SNTs / QD1 assembled with one layer of quantum dots is slightly lower than the fluorescence intensity of CdSe / CdS / ZnS QDs itself, which may be due to the aggregation-induced quenching caused by the dense assembly of quantum dots. However, when the second layer of quantum dots is successfully assembled, the relative fluorescence intensity will increase, and the relative fluorescence intensity of the assembly will continue to increase after the introduction of the third layer of quantum dots. It can be seen that the fluorescence intensity has been significantly improved due to the assembly of more quantum dots. When the phase transfer strategy and silica coating strategy are carried out, the fluorescence intensity of the material will be slightly reduced, which may be due to the loss of assembly materials during operations such as washing and centrifugation and the scattering effect caused by the coated silica material.
[0064] 6. Preparation of Carboxylated STQS-COOH Tubular Assemblies
[0065] The above STQS was dissolved in 40 mL of ethanol, followed by the addition of 1 mL of ammonia and 40 μL of 3-aminopropyltriethoxysilane (APTES), and stirred at room temperature for 12 h to obtain amino-modified STQS-NH2. The excess APTES was then removed by washing with ethanol, dispersed in 20 mL of N,N-dimethylformamide (DMF), and 100 mg of succinic anhydride was added, and stirring was continued for 4 h to obtain carboxyl-modified STQS microtubes (STQS-COOH), which were then washed several times with ethanol and water.
[0066] 7. STQS-COOH tubular assembly coupled to antibody
[0067] The monoclonal antibody of SARS-CoV-2NP (AB0046-2, Nanjing Baikang Biological) was coupled with STQS-COOH by the typical carbodiimide-assisted coupling method. The specific steps are as follows:
[0068] First, 2 mg of STQS-COOH, 2 mg of N-hydroxysulfosuccinimide sodium salt (Sulfo-NHS) and 1 mg of carbodiimide hydrochloride (EDC) were dissolved and dispersed in 1 mL of PB (pH = 6.0, 0.01 mol / L) buffer solution, incubated at room temperature by shaking for 30 min, then centrifuged at 10000 rpm for 5 min, the supernatant was discarded, the precipitate was redispersed in 1 mL of PB (pH = 7.4, 0.01 mol / L) buffer solution, and 0.04 mg of SARS-CoV-2NP antibody (AB0046-2, Nanjing Baikang Biological) was added, and the mixture was mixed by ultrasonication for 30 s and then continued to be incubated at room temperature by shaking for 2.5 h. Subsequently, the mixture was centrifuged at 10000 rpm for 5 min, the supernatant was discarded, the precipitate was redispersed in 1 mL of PB (pH = 7.4, 0.01 mol / L, containing 1% BSA) blocking solution, and the mixture was blocked at room temperature by shaking for 2 h. After the reaction was completed, the precipitate was collected by centrifugation at 10,000 rpm, washed twice with PB (pH = 7.4, 0.01 mol / L) buffer solution, and finally dispersed into 1 mL PB (pH = 7.4, 0.01 mol / L) buffer solution to obtain the iSTQS signal probe, which was stored at 4°C for subsequent use.
[0069] 8. Preparation of immunochromatographic test strips
[0070] First, the sample pad was treated with sample pad treatment solution (pure water, containing 1.2% Tris, 0.12% EDTA, 0.04% sodium caseinate, 1% trehalose, 0.5% Tween-20, pH = 7.4) and dried overnight at 37 ° C. SARS-CoV-2NP monoclonal antibody (AB0046-1, Nanjing Baikang Biology) (2 mg / mL) and goat anti-mouse IgG antibody (1 mg / mL) were fixed on the T line and C line of the NC membrane with a film spraying instrument at a dosage of 0.75 μL / cm, and then dried overnight at 37 ° C. Finally, the absorption pad, NC membrane and sample pad were assembled in sequence, and cut into 3 mm wide strips with a strip cutter and sealed and stored under dry conditions.
[0071] 9. Immunochromatographic detection of SARS-CoV-2 NP antigen
[0072] Use 10mM PBS buffer solution (pH=7.4) containing 0.1% sodium caseinate, 0.2% BSA, 0.4% Tween, and 0.2% PVP360 to dilute the SARS-CoV-2NP antigen to a certain concentration. The concentration range of the antigen is 0-500ng / mL. 80μL of sample solution containing different concentrations of SARS-CoV-2NP antigen and 2ug of iSTQS signal probe are fully mixed and dripped onto the sample pad, and flow through the NC membrane to the absorption pad under capillary action. As the antigen concentration increases, the T line gradually changes from colorless to red, and the C line remains red. After 10 minutes, use a smartphone to take pictures under the excitation of any model of small ultraviolet banknote detector lamp (365nm excitation light). Fluorescent photos of fluorescent lateral flow immunochromatographic test strips in the concentration range of 0-500ng / mL SARS-COV-2NP antigen are shown in the figure. Fig. 9 shown.
[0073] 10. Mobile quantitative analysis of immunochromatography platform
[0074] Then, based on the test results of step 9, the color recognition software Color Picker on the smartphone was used to read the R value of the T line (the R value channel of the T line photo image), and a standard curve was drawn with the SARS-COV-2NP antigen concentration as the horizontal axis and the R value as the vertical axis. The results are shown in Fig.10 .from Fig.10 It can be seen from the standard curve that the nonlinear curve fitting range of the new crown N protein concentration is 0-500ng / mL, and the corresponding R 2 is 0.989; the linear range is 0-2ng / mL, and the corresponding R 2 The linear range was 0.982, which showed a good linear range and obtained a quantitative detection limit of 0.019 ng / mL with a naked eye detection limit of 0.02 ng / mL. Therefore, a good linear relationship and detection sensitivity can be obtained using the signal reading model.
[0075] 11. Instrument-side quantitative analysis of immunochromatography platform
[0076] For the test results of step 9, a commercial strip reader was used to measure the R signal intensity of the T line (the commercial strip reader was provided by the Shenzhen Institute of Nanotechnology, Chinese Academy of Sciences, model TND09-MJ). A standard curve was drawn with the SARS-COV-2NP antigen concentration as the horizontal axis and the R signal intensity of the T line measured by the commercial strip reader as the vertical axis. The results are shown in Fig.11 .from Fig.11 It can be seen from the standard curve that the nonlinear curve fitting range of the new crown N protein concentration is 0-500ng / mL, and the corresponding R 2 is 0.996; the linear range is 0-0.2ng / mL, and the corresponding R 2The linear range was 0.962, which showed a good linear range and achieved a quantitative detection limit as low as 0.081 ng / mL.
[0077] Embodiment 2:
[0078] The operations of step 1 to step 3 of Example 1 were repeated, except that the following operating conditions were changed in step 3:
[0079] 1) In the operation steps of a layer assembly of quantum dots (QDs), the volume of QDs toluene solution (10 mg / mL) is 0.2 mL-1 mL, the total feed ratio of QDs is 20% to 100%, and other operating conditions remain unchanged. Finally, a series of one-layer assemblies SNTs / QD1 under different QDs feed ratios are obtained.
[0080] 2) Using the one-layer assembly SNTs / QD1 prepared under the condition of 100% QDs feed ratio, the two-layer assembly operation of QDs was continued. The difference was that the volume of QDs toluene solution (10 mg / mL) was 0.2 mL to 1 mL, so that the total QDs feed ratio range was 120% to 200%. Other operating conditions remained unchanged, and finally a series of two-layer assemblies SNTs / QD2 under different quantum dot QDs feed ratios were prepared.
[0081] 3) Using the two-layer assembly SNTs / QD1 prepared at a QDs feed ratio of 200%, the three-layer assembly of QDs was continued. The difference was that the volume of QDs toluene solution (10 mg / mL) was 0.2 mL to 1 mL, so that the total QDs feed ratio range was 220% to 300%. Other operating conditions remained unchanged, and finally a series of three-layer assemblies SNTs / QD3 were prepared under different quantum dot QDs feed ratios.
[0082] During the above one to three-layer assembly process, the performance tests were performed on the assemblies prepared under different QDs feed ratios. The test method steps are as follows:
[0083] The corresponding relationship between the quantum dot assembly rate and the quantum dot feed ratio in the assembly is shown in the attached Figure 4 The illustrations in Figure a are sunlight photos of the supernatant (upper) and the assembly dispersed in toluene solution (lower) after the quantum dots were assembled at different stages. Figure 4 As can be seen from the sub-figure a of , for each layer of quantum dots, the assembly rate will reach saturation as the feed ratio increases, so it is necessary to find the inflection point where the assembly rate reaches saturation to ensure that the material is assembled with as many quantum dots as possible to improve the optical properties of the material. In addition, the relationship between the fluorescence intensity of the quantum dot assembly and the quantum dot assembly rate can be found in the attached Figure 4 Component b of . Figure 4 The quantum dot assembly rate in sub-graph b is Figure 4 It corresponds to the assembly rate in sub-figure a. Figure 4 The quantum dot assembly rate in sub-figure b is the result of assembling one, two, and three layers together.
[0084] Figure 4 The assembly of the second and third layers of quantum dots is carried out on the premise that the assembly of the previous layer has reached saturation. The second layer continues to be fed on the basis of 100% of the first layer, and the third layer continues to be fed on the basis of 100% of the second layer. The quantum dot feed ratio is the mass ratio of the oil phase quantum dots to the silicon template. The quantum dot assembly rate is quantitatively detected by a fluorescence instrument. The quantum dot assembly rate in the assembly = (fluorescence intensity of the quantum dot stock solution - fluorescence intensity of the upper clear liquid after centrifugation) / fluorescence intensity of the quantum dot stock solution * quantum dot feed ratio.
[0085] In addition, it can be seen from the assembly results of one to three layers that PAMA-NH2 polymer filling is important for increasing the assembly amount of quantum dots.
[0086] Embodiment 3:
[0087] The preparation process of the STQS tubular assembly in Example 1 was repeated, except that the red QDs were replaced with red QDs, blue QDs or green QDs of equal mass, thereby finally obtaining red STQS, blue STQS or green STQS respectively. The red QDs, blue QDs and green QDs, as well as the red STQS, blue STQS or green STQS were tested for fluorescence intensity, and the measured fluorescence intensity was normalized. The test results are shown in Figure 5 As shown in a, Figure 5 The inset of a is the fluorescence photograph of the suspension of red STQS, blue STQS or green STQS, respectively. Figure 5 The experimental results of a show that for quantum dots of the same color, the fluorescence emission wavelength does not change before and after quantum dot assembly, ensuring the performance of the material.
[0088] Embodiment 4:
[0089] Compare the performance of hollow silicon tube assembly materials and solid spherical assembly materials:
[0090] The hollow tubular template is the hollow silica nanotubes SNTs prepared in step 1 of Example 1.
[0091] The preparation process of the solid spherical template comprises the following steps:
[0092] 1) Mix 40 ml of ethanol, 2.43 ml of deionized water and 1.8 ml of ammonia water and heat to 55° C. under vigorous stirring. Quickly mix 4 ml of ethanol and 1.55 ml of TEOS and add to the above solution, and stir at 55° C. for 5 hours.
[0093] 2) Take 10 ml of the above reaction solution, add 70 ml of ethanol into a 250 ml bottle, add 7.5 ml of ammonia water, add 1 ml of TEOS and 10 ml of ethanol dropwise under stirring at room temperature, and react for 5 hours. Then add 1 ml of TEOS and 10 ml of ethanol to the above system and continue the reaction for 5 hours.
[0094] 3) Finally, 266ul TEOS and 3ml ethanol were added upward into the system and reacted for 80min. The solid silicon template dsi was obtained and stored in ethanol (dispersion concentration was about 10mg / mL).
[0095] In order to facilitate the comparison of the performance of hollow silica tube assembly materials and solid spherical assembly materials, theoretical calculations are required to control the number of quantum dots assembled by a single number of hollow silica tube assemblies and solid spherical assemblies to be the same, so that the two materials can be assembled unsaturatedly. The theoretical calculation process is described as follows.
[0096] According to the electron microscope image of the material and the measurement results of nano measurer software, the diameter (2r) of the solid spherical template dSI is 145nm; 实心球 =(4 / 3)πr 3 , m = ρ SiO2 V. The mass m of a single solid silicon sphere of this size can be calculated to be: 3.52×10 -12 mg.
[0097] The long axis (2a1) of the hollow tubular template is 139 nm, and the short axis (2b1) is 36 nm, wherein the long axis (2a2) of the cavity is 121 nm, and the short axis (2b2) is 21 nm; 空心管 =a1×b1 2 ×π-a2×b2 2 ×π,m=ρ SiO2 V; the mass m of a single hollow tubular template of such a particle size can be calculated as: 2.2×10 -13 mg.
[0098] That is, for a single material, the mass of a single solid silicon sphere is 16 times the mass of a single hollow tubular template. If 10 mg of material is taken, the number of hollow tubular materials is 16 times the number of solid silicon spheres N. Therefore, in order to control the assembly of the same number of quantum dots on two single materials, for the same mass of two materials, the assembly rate of hollow tubular materials QDs should be 16 times that of solid spherical materials.
[0099] The obtained from Example 2 Figure 4 The results show that for hollow tubular materials, when the feed ratio is 20%, the assembly rate is 12%. From the above calculations, it can be seen that for the same mass of solid spherical materials, the assembly rate should be 0.75%. From the assembly supernatant of solid spherical materials, when the feed ratio is 0.75%, the supernatant is colorless, and the fluorescence detector can hardly detect the fluorescence value, proving that the assembly rate is 0.75%. Through the above theoretical calculations, the number of QDs assembled from the two single materials is controlled to be the same.
[0100] A hollow tubular assembly structure is prepared from a hollow tubular template raw material by repeating the operating steps of step 2 to step 6 of Example 1, with the only difference being that the following operating conditions are changed in step 3: only one layer of QDs is assembled, the volume of the QDs toluene solution (10 mg / mL) is 0.2 mL, the total feed ratio of QDs is 20%, and other operating conditions remain unchanged.
[0101] The solid spherical assembly structure is prepared from a solid spherical template, that is, the operating steps of step 2 to step 6 of Example 1 are repeated, the only difference is that the following operating conditions are changed in step 3: only one layer of quantum dots QDs is assembled, the volume of QDs toluene solution (10 mg / mL) is 0.075 mL, the total feed ratio of QDs is 0.75%, and other operating conditions remain unchanged.
[0102] The influence of light scattering intensity on fluorescence intensity caused by shape effect (Figure S6) was verified as follows: two assembly structure materials with different numbers of particles were dispersed in 1 mL of ethanol, the fluorescence intensity of the assembly materials was measured, and multiple points were taken as linear slopes. The ratio of the slopes is the ratio of fluorescence signal intensity amplification. The test results are shown in Figure S6.
[0103] Immunokinetic validation scheme for shape effect solution (Figure S7):
[0104] (1) FITC fluorescent dye labeled streptavidin (SA)
[0105] 1. Dissolve FITC fluorescent dye in deionized water at a concentration of 10 mg / mL and mix thoroughly to completely dissolve the FITC fluorescent dye;
[0106] 2. Dissolve 1 mg of SA in 0.5 mL of 50 mM boric acid buffer (pH = 8.5), add excess FITC fluorescent dye (the molar amount of FITC fluorescent dye is 18 times the molar amount of streptavidin (SA)), and immediately mix the reactants;
[0107] 3. Incubate in the dark at room temperature for 1 hour;
[0108] 4. Ultrafilter out excess FITC fluorescent dye.
[0109] (2) Two carboxyl materials were coupled with biotin to prepare probes: 2 mg of the hollow tubular assembly structure or the solid spherical assembly structure was dissolved with 2 mg of N-hydroxysulfosuccinimide sodium salt (Sulfo-NHS) and 1 mg of carbodiimide hydrochloride (EDC) in 1 mL of PB (pH = 6.0, 0.01 mol / L) buffer solution, incubated on a shaker at room temperature for 30 min, then centrifuged at 10,000 rpm for 5 min, the supernatant was discarded, the precipitate was redispersed in 1 mL of PB (pH = 7.4, 0.01 mol / L) buffer solution, and 0.04 mg of biotin was added. After mixing by ultrasonication for 30 s, the mixture was incubated on a shaker at room temperature for 2.5 h.
[0110] (3) Take two materials with the same number of particles and add the same concentration of FITC-labeled SA (nBiotin:nSA=1:8) in 10mM PB buffer (pH=7.4) and react at room temperature for 15 minutes. Centrifuge the solution after the reaction and measure the fluorescence intensity of SA-FITC fluorescence in the supernatant. Repeat the above experiment with different numbers of particles for each material to obtain Figure 7 Results: The lower the fluorescence intensity of the supernatant, the better the solution immunokinetics of the material.
[0111] Figure 6-Figure 7 The particle number of a material refers to the amount of material dispersed in the solvent, and the particle number of the material can be measured by an instrument.
[0112] Shape effect test strips ( Figure 8 )Immunokinetics validation scheme:
[0113] 1. Preparation of SA-Biotin system test strips: First, treat the sample pad with sample pad treatment solution (pure water, containing 1.2% Tris, 0.12% EDTA, 0.04% sodium caseinate, 1% trehalose, 0.5% Tween-20, pH = 7.4), and dry overnight at 37°C. Fix SA at 1 mg / mL on the T line of the NC membrane using a film spray gold instrument at a dosage of 0.75 μL / cm, and then dry overnight at 37°C. Finally, assemble the absorption pad, NC membrane and sample pad in sequence, and cut them into 3 mm wide strips with a strip cutter and seal them for storage under dry conditions.
[0114] 2. SA-Biotin system immunochromatographic detection: Add probes (coupled with Biotin) containing two assembly structures with different numbers of particles to 80 μL of 10 mM PBS buffer solution (pH = 7.4) (containing 0.1% sodium caseinate, 0.2% BSA, 0.4% Tween, 0.2% PVP360), mix thoroughly and drip onto the sample pad, and flow to the absorption pad through the NC membrane under capillary action. As the number of probe particles increases, the T line gradually changes from colorless to red. Use Color Picker to read the R value of the T line, and compare the number of particles at the first signal mutation point to determine the kinetic effects of the two assembly structure probes. The fewer the number of particles at the signal mutation point, the better the kinetic effect of the probe, which can improve the sensitivity of the chromatography platform.
[0115] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. A method for preparing a high recognition, low scattering quantum dot tubular assembly structure immunochromatographic probe, characterized in that In the presence of a surfactant, Ni salt reacts with hydrazine hydrate to form nickel-hydrazine complex nanorods, and then silica is coated using a sol-gel process, and then selectively etched with hydrochloric acid to obtain one-dimensional hollow tubular silica nanotubes SNTs; the SNTs are thiol-modified to obtain SNTs-SH, and SNTs-SH is used as a carrier, and CdSe / CdS / ZnS red quantum dots (QDs) are used as signal tags. Multilayer assembly of quantum dots is performed on the carrier SNTs-SH to construct an oil-soluble tubular assembly dSi / tQD, and then n-octyltrimethoxysilane (OTMS) is used to cause a hydrolysis condensation reaction on the surface of the tubular assembly to achieve a phase transfer of the tubular assembly from an organic phase to an aqueous phase, and then the tubular assembly is etched by a slurry-free reactor. The method utilizes tetraethyl orthosilicate (TEOS) to hydrolyze and deposit a thin layer of silica to improve the stability of the internally assembled quantum dots. Then, the amino groups are modified by 3-aminopropyltriethoxysilane and the carboxyl groups are modified by succinic anhydride to obtain STQS-COOH. The carboxyl-modified assembly STQS-COOH is coupled to a labeled antibody and blocked with a blocking solution containing BSA to finally obtain a probe.
2. The method for preparing a high recognition, low scattering quantum dot tubular assembly structure immunochromatographic probe according to claim 1, characterized in that The method for preparing the one-dimensional hollow tubular silica nanotubes SNTs specifically comprises the following steps: S1: dissolving the surfactant Brij58 in cyclohexane, stirring at 45-55°C, adding Ni salt, and then adding hydrazine hydrate dropwise, stirring and reacting for 2.8-3.2h, so that the Ni salt reacts with hydrazine hydrate to form nickel-hydrazine complex nanorods; S2: then add diethylamine and TEOS to the system of step S1, continue stirring and reacting for 1.5-2.5 hours to allow the silicon dioxide to precipitate, centrifuge and wash after the reaction is completed; S3: The product obtained in step S2 is dispersed in a 0.8-1.2M hydrochloric acid solution, stirred at room temperature for 0.5-2h for selective etching, and then the product is collected by centrifugation and washed with water until the pH is neutral to obtain one-dimensional hollow tubular silica nanotubes SNTs, which are stored in anhydrous ethanol.
3. The method for preparing a high recognition, low scattering quantum dot tubular assembly structure immunochromatographic probe as claimed in claim 2, characterized in that In step S1, the surfactant is Brij58, and its solubility concentration in cyclohexane is 0.5-0.6 g / mL; the molar ratio of hydrazine hydrate to Ni salt is 4-10:1, and the solubility concentration of Ni salt in cyclohexane is 50-100 mmol / L; The volume ratio of diethylamine to TEOS in step S2 is 0.4-0.6:1, the volume ratio of TEOS in step S2 to the amount of Ni salt in step S1 is 1:0.5-0.8, the volume unit is mL, and the amount unit is mmol.
4. The method for preparing a high recognition, low scattering quantum dot tubular assembly structure immunochromatographic probe according to claim 1, characterized in that The process of multilayer assembly of quantum dots on the template SNTs-SH is as follows: 1) Assembly of the first layer of quantum dots: Take a toluene solution of CdSe / CdS / ZnS quantum dots, add the template SNTs-SH, and ultrasonicate for 7-10 minutes to obtain a uniform solution, then collect the precipitate by centrifugation, and after the residual toluene solvent in the precipitate evaporates, an assembly of a layer of quantum dots SNTs / QD1 is obtained; the mass ratio of the template SNTs-SH to the CdSe / CdS / ZnS quantum dots is 1:0.8-1.0; 2) Coating of amino dendritic polymer: adding the assembly product obtained in step 1) to an ethanol solution containing amino dendritic polymer polyamide PAMA-NH2, ultrasonicating for 7-10 minutes, and removing the supernatant by centrifugation to obtain the nanocomposite SNTs / QD-PAMA with the outermost layer coated by amino groups, and then using the amino groups rich on its surface to coordinate with quantum dots, the subsequent assembly of quantum dots is continued; 3) Repeat the above steps 1)-2) to achieve multi-layer alternating assembly of quantum dots in the organic phase and amino dendritic polymer polyamide PAMA-NH2, assembling a total of 2-4 layers of quantum dots, preferably assembling 3 layers of quantum dots, and finally obtaining the constructed oil-soluble assembly SNTs / tQD product.
5. The method for preparing a high recognition, low scattering quantum dot tubular assembly structure immunochromatographic probe according to claim 1, characterized in that The process of coupling the carboxyl-modified assembly with the labeled antibody and blocking with a blocking solution containing BSA: adding the carboxyl-modified assembly to a pH=6.0 PB buffer, adding N-hydroxysulfosuccinimide sodium salt (Sulfo-NHS) and carbodiimide hydrochloride (EDC), and incubating in a shaker for 20 to 40 minutes; then collecting the product by centrifugation; The product was resuspended in pH = 7.4 PB buffer, the labeled antibody was added, and the reaction was carried out on a shaking table for 2 to 3 hours. After the reaction was completed, the product was centrifuged and blocked with pH = 7.4 PB buffer containing 0.5-2% BSA for 1.5-3 hours. The tubular probe was then collected by centrifugation, washed with pH = 7.4 PB buffer, and stored in pH = 7.4 PB buffer for refrigeration.
6. A high recognition, low scattering quantum dot tubular assembly structure immunochromatographic probe prepared by the method according to any one of claims 1 to 5.
7. The use of a high recognition, low scattering quantum dot tubular assembly structure immunochromatographic probe as claimed in claim 6, characterized in that The probe is used to detect the corresponding antigen, comprising the following steps: S1 Construction of immunochromatographic test strip: The immunochromatographic test strip includes a sample pad, a NC membrane and an absorption pad assembled in sequence on a plastic base plate, and the T line and C line of the NC membrane are coated with a capture antibody and a goat anti-mouse IgG antibody, respectively; S2 antigen concentration detection: dilute the antigen with pH=7.4 PBS buffer containing 0.05-0.2% sodium caseinate, 0.1-1% BSA, 0.1-1% Tween 20 and 0.1-0.5% PVP360, prepare a series of standard solutions with different antigen concentrations, add the probe to the standard solution and mix thoroughly, drip it onto the sample pad of the test strip respectively, flow to the absorption pad through the NC membrane under capillary action, after 5-20 minutes, use a smart phone to take pictures under the excitation of 365nm excitation light of ultraviolet lamp, obtain images of T line and C line of the test strip, use ColorPicker, a color recognition software of the smart phone, to read the R value of the photo image of the T line, and draw a standard curve with R value as the ordinate and antigen concentration as the abscissa.
8. The use according to claim 7, characterized in that The labeled antibody is monoclonal antibody 2 of SARS-CoV-2NP, the capture antibody is monoclonal antibody 1 of SARS-CoV-2NP, and the antigen is SARS-CoV-2NP antigen.
Citation Information
Patent Citations
Rapid detection method employing ultrasensitive quantum dot microsphere immunity-chromatograph test paper strips
CN101893623A
Ratiometric fluorescent probe based on ion imprinting, preparation and application thereof
CN106833646A
Ratiometric fluorescent probe and preparation thereof, and application of ratiometric fluorescent probe in detection of glutathione
CN107603593A
Optical probe based on gold nanoparticle efficient assembly structure, and preparation method and application of optical probe
CN109752536A
Quantum dot dual-emission ratiometric fluorescent probe, preparation method and applications thereof
CN110776916A